2020
DOI: 10.1016/s2214-109x(20)30127-3
|View full text |Cite
|
Sign up to set email alerts
|

Physical multimorbidity, health service use, and catastrophic health expenditure by socioeconomic groups in China: an analysis of population-based panel data

Abstract: Background Multimorbidity, the presence of two or more mental or physical chronic non-communicable diseases, is a major challenge for the health system in China, which faces unprecedented ageing of its population. Here we examined the distribution of physical multimorbidity in relation to socioeconomic status; the association between physical multimorbidity, health-care service use, and catastrophic health expenditures; and whether these associations varied by socioeconomic group and social health insurance sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
230
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(250 citation statements)
references
References 36 publications
(60 reference statements)
17
230
2
1
Order By: Relevance
“…The other four papers reported national prevalence of multimorbidity among middle-aged and elderly Chinese. [18][19][20][21] These papers all used the same data set from the China Health and Retirement Longitudinal Study and reported consistently higher prevalence of multimorbidity among urban population than rural population. Zhao et al, for example, reported that rurality was associated with an OR of 0.76 of multimorbidity in people above 50 years old.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…The other four papers reported national prevalence of multimorbidity among middle-aged and elderly Chinese. [18][19][20][21] These papers all used the same data set from the China Health and Retirement Longitudinal Study and reported consistently higher prevalence of multimorbidity among urban population than rural population. Zhao et al, for example, reported that rurality was associated with an OR of 0.76 of multimorbidity in people above 50 years old.…”
Section: Open Accessmentioning
confidence: 99%
“…Zhao et al, for example, reported that rurality was associated with an OR of 0.76 of multimorbidity in people above 50 years old. 21 These studies have two important limitations. First, measurement of multimorbidity was all based on selfreport.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 However, our study utilized clinical measurement for all physical NCDs as well as mental disorder which can mitigate under-reporting of NCDs. 42 Additionally, this survey only asked if subjects were taking treatment (medicines, lifestyle changes), but did not measure self-reported treatment adherence (i.e. dosage, frequency, duration, etc).…”
Section: Comparison With Literaturementioning
confidence: 99%
“…4,5 One study found the prevalence of multi-morbidity in an urban community-dwelling elderly to be 49.4%, 6 while data from the China Health and Retirement Longitudinal Study showed that multi-morbidity of physical conditions increased with age and was more common in poorer regions. 7 Elderly patients often need to use polypharmacy because of multiple chronic diseases. 8 A study in western China showed that older people's use of medicines was higher in urban than rural areas, with 17.5% and 11.5% of residents in these areas, respectively, using five or more medicines.…”
Section: Introductionmentioning
confidence: 99%